Several simple remarks concerning the attractiveness and usefulness of “Kangaroo” problems - Rudalevičienė, Regina; Kašuba, Romualdas (Lietuvos matematikos rinkinys, 2011)
In the paper some aspects of natural attractiveness and practical usefulness of “Kangaroo” problems for individual students and for the teaching of math are discussed.
Keywords: “Kangaroo” competition; mathematical education; school didactics; naturalism of tasks; attractiveness of tasks; individualization of tasks